Like this presentation? Why not share!

# Polynomial Powerpoint

## by kmspruill on Oct 21, 2009

• 13,998 views

### Views

Total Views
13,998
Views on SlideShare
11,225
Embed Views
2,773

Likes
0
180
0

### 6 Embeds2,773

 http://wpmu.bionicteaching.com 2458 http://nilemathclass.wordpress.com 276 http://tmklive.org 27 http://www.slideshare.net 6 http://us-w1.rockmelt.com 5 http://translate.googleusercontent.com 1

### Categories

Uploaded via SlideShare as Microsoft PowerPoint

## Polynomial PowerpointPresentation Transcript

• (3x2 + 5x + 3) + (2x2 – 3x + 1)
• (3x2+ 5x + 3) + (2x2 – 3x + 1)
• (3x2+ 5x + 3) + (2x2– 3x + 1)
• (3x2+ 5x+ 3) + (2x2– 3x + 1)
• (3x2+ 5x+ 3) + (2x2– 3x + 1)
• (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2=
• (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x2
• (3x2+ 5x+ 3) + (2x2– 3x + 1) 3x2 + 2x2= 5x25x – 3x =
• (3x2+ 5x+ 3) + (2x2– 3x + 1) 3x2 + 2x2= 5x25x – 3x = 2x
• (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x25x – 3x = 2x3 + 1 =
• (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x25x – 3x = 2x3 + 1 = 4
• (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x25x – 3x = 2x3 + 1 = 4
5x2+ 2x + 4
• (6x – 4y + 2z) – (2x + 7y – 4z)
• (6x – 4y + 2z) – (2x + 7y – 4z)
• (6x – 4y + 2z) – (2x + 7y – 4z)
• (6x – 4y + 2z) – (2x + 7y – 4z)
• (6x – 4y + 2z) – (2x + 7y – 4z)
• (6x – 4y + 2z) – (2x + 7y – 4z)
• (6x– 4y + 2z) – (2x+ 7y – 4z)
• (6x– 4y + 2z) – (2x+ 7y – 4z)
• (6x– 4y + 2z) – (2x+ 7y – 4z)
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x =
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y =
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11y
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11x2z + 4z =
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11x2z + 4z = 6x
• (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11x2z + 4z = 6z
4x– 11y + 6z
• AlgeBlocks
y
x2
x
1
y
x2
x
1
• (2x2 + 3x + 1) + (x2 + 2x + 4)
• (2x2 + 3x + 1) + (x2 + 2x + 4)
x2
x2
x2
x
x
x
x
x
1
1
1
1
1
• 3x2 + 4x + 5
x2
x2
x2
x
x
x
x
1
1
1
1
1
• (5x – 4y ) + (2x + y)
• (5x – 4y ) + (2x + y)
x
x
x
x
x
x
x
y
y
y
y
y
• x
x
x
x
x
x
x
y
y
y
y
y
• x
x
x
x
x
x
x
y
y
y
y
y
• x
x
x
x
x
x
x
y
y
y
• 7x – 3y
x
x
x
x
x
x
x
y
y
y
• (x2 – 3x + 2) – (4x2 + x – 4)
• (x2 – 3x + 2) – (4x2 + x – 4)
• (x2 – 3x + 2) – (4x2 + x – 4)
• (x2 – 3x + 2) – (4x2 + x – 4)
x2
x2
x2
x2
x2
x
x
x
x
1
1
1
1
1
1
• x2
x2
x2
x2
x2
x
x
x
x
1
1
1
1
1
1
• x2
x2
x2
x2
x2
x
x
x
x
1
1
1
1
1
1
• x2
x2
x2
x
x
x
x
1
1
1
1
1
1
• -3x2 – 4x + 6
x2
x2
x2
x
x
x
x
1
1
1
1
1
1